Vigabatrin in pediatric patients with refractory epilepsy - Turanli, Güzide; Celebi, Asli; Yalnizoğlu, Dilek; Topçu, Meral; Topaloğlu, Haluk; Banu, Anlar; Aysun, Sabiha (The Turkish Journal of Pediatrics, 2006)
New generation antiepileptic medications have improved seizure outcome in patients with intractable epilepsy. We studied the efficacy and side effect profile of vigabatrin (VGB) in pediatric patients with intractable seizure disorder. We reviewed the database of our short-term video-EEG monitoring laboratory to screen patients with intractable epilepsy who were on VGB either alone or in combination for three months or more. We subsequently reviewed the medical records of these patients to abstract clinical information regarding age, sex, seizure type, epilepsy syndrome, efficacy and side effects of VGB. Of 111 patients, 75 (68%) were male and 36 (32%) female. Seizure onset was during the newborn period in 12 patients (11%), during the first year of life beyond the newborn period in 47 patients (42%), between 1-5 years in 23 patients (21%), and above five years in the remaining 29 patients (26%). Fifty-four patients (48.6%) had partial onset seizures with or without secondary generalization; 49 patients (44.1%) had primary generalized seizures; 8 patients (7.2%) had two or more types of seizure. Fifty-three percent of patients had mental retardation, and 35% had abnormal findings on physical/ neurological examination. Of 98 patients, 70 (71.4%) had abnormal magnetic resonance imaging (MRI) findings. Ninety-seven percent of patients had been on polytherapy before VGB was added to treatment. VGB reduced seizure frequency by at least 50% in 33.3% of patients with partial seizures, and in 30.6% of patients with primary generalized seizures. Six of the responders with partial seizures had complete resolution of their seizures. Most common side effects included visual field defects, increased appetite and obesity. Vigabatrin seems to be more effective in partial seizures in childhood intractable epilepsy. Patients should be closely monitored regarding side effects of VGB.